Moralny obowiązek ochrony środowiska naturalnego według ks. prof. Tadeusza Ślipko - Stefan Konstańczak (Studia Ecologiae et Bioethicae)
In his paper, the author makes an attempt at reconstructing one of the first propositions in Poland to start a philosophical discourse on ecological problems. The author of this proposition is priest Tadeusz Ślipko. According to this author the problems of the moral aspects of natural environmental protection are also bioethical problems. Therefore, we can see that he does not consider ethics of the environment as an individual philosophical discipline. The article concentrates on presenting the sources and the range of moral duties of humankind towards the natural environment. Tadeusz Ślipko does not approve of the anthropocentric or biocentric standpoints in the issues of natural environmental protection. He offers his own idea of anthropopriorism, which takes the middle ground between these two extreme concepts. In conclusion, the author underlines that there is still a strong need for ethical reflection over the state of the natural environment along the lines of Ślipko’s stance.